Molecular Differentiation of Mitochondrial NADH Dehydrogenase Subunit-4 and Phylogeny of the Genus Pangshura - Baruah, Chittaranjan; Devi, Papari; Sharma, Dhirendra K. (Asian Journal of Biological and Life Sciences, 2016)
Abstract: The turtle family Geoemydidae comprising mostly of freshwater turtles includes several highly endangered Southeast Asian turtle species. The present study has been performed on the mitochondrial NADH dehydrogenase 4 (ND4) gene sequence analysis and phylogeny of the Southeast Asian turtle genus Pangshura (Testudines: Geoemydidae: Pangshura). A comparative in silico study has been carried out at the transcriptional and translational level for mRNA structure along with structure and evolution of NADH dehydrogenase enzyme. Evolutionary analyses were conducted by using the methods of Maximum Parsimony, Maximum Likelihood and Neighbor-Joining. Sequence analyses, restriction mapping and RNA structure prediction were performed in the CLC Genomics Workbench 4.0 (CLC Bio, Cambridge, MA, USA). Comparative modeling of NADH4 was conducted by using Modeller9v2 program. The study reveals that P. smithii and P. tentoria are the sister species followed by P. tecta and P. sylhetensis their successive sister-taxa. Distinctness within the sub-species of P. tentoria is not clear in the evolutionary data of ND4 gene and encoded NADH protein. Although, sequence variation has been observed in ND4 gene, minor structural changes have been observed in some parts of mRNA secondary structure with variation in the minimum folding energy. The computational models of NADH dehydrogenase 4 could be of use for further evaluation of molecular mechanism of function. The present study also provides an indispensable groundwork for future conservation and genetic analysis of other turtle genera.
Keywords: Chelonian; Conservation; Geoemydidae; In-silico; NADH